2017
DOI: 10.1097/acm.0000000000001735
|View full text |Cite
|
Sign up to set email alerts
|

Well-Being in Graduate Medical Education: A Call for Action

Abstract: Job burnout is highly prevalent in graduate medical trainees. Numerous demands and stressors drive the development of burnout in this population, leading to significant and potentially tragic consequences, not only for trainees but also for the patients and communities they serve. The literature on interventions to reduce resident burnout is limited but suggests that both individual- and system-level approaches are effective. Work hours limitations and mindfulness training are each likely to have modest benefi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
0
13

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(89 citation statements)
references
References 26 publications
4
70
0
13
Order By: Relevance
“…Faculty should role model professional behaviors for residents in managing the prevention and response to clinical adversities encountered in training. Heathcare organizations should provide peer support to any resident involved in emotionally stressful situations [63]. Indeed, the Charter on Physician Well-Being aims in part to remind physicians of their responsibility to examine the culture of medicine and how it facilitates meaning, fulfillment in practice, and professionalism and to encourage a supportive culture [64].…”
Section: Professional Responsesmentioning
confidence: 99%
“…Faculty should role model professional behaviors for residents in managing the prevention and response to clinical adversities encountered in training. Heathcare organizations should provide peer support to any resident involved in emotionally stressful situations [63]. Indeed, the Charter on Physician Well-Being aims in part to remind physicians of their responsibility to examine the culture of medicine and how it facilitates meaning, fulfillment in practice, and professionalism and to encourage a supportive culture [64].…”
Section: Professional Responsesmentioning
confidence: 99%
“…A pilot study in a single residency program suggested that EM faculty were quite poor in being able to accurately predict burnout among EM trainees . Because wellness habits, like many other practices, may be “imprinted” during residency training, focusing on the role of burnout and other related states in the unique environment of academic medicine has the potential for long‐lasting effects for both individual physicians and the specialty.…”
Section: Research Priority 2: Early Training and The Learning Environmentioning
confidence: 99%
“…Burnout has been linked to adverse effects in health care providers, including higher rates of depression, increased suicidal ideation and increased rates of medical errors . Furthermore, the American Council for Graduate Medical Education (ACGME) has recently raised resident burnout as an issue of high importance, experts have called for a national response, and newly formed collaborations across medical disciplines are working to address this topic . Research suggests that ‘supportive working environments’ and ‘celebrating accomplishments’ protect against burnout, yet there is a dearth of evidence on how to foster such supportive environments in residency.…”
Section: Introductionmentioning
confidence: 99%
“…1 Furthermore, the American Council for Graduate Medical Education (ACGME) has recently raised resident burnout as an issue of high importance, 2 experts have called for a national response, 3 and newly formed collaborations across medical disciplines are working to address this topic. 4 Research suggests that 'supportive working environments' and 'celebrating accomplishments' protect against burnout, 5 yet there is a dearth of evidence on how to foster such supportive environments in residency. In this article, we describe outcomes of the 'Golden Ticket Project' (GTP), a resident-led programme that encourages peer-to-peer support and the recognition of positive behaviours and attitudes.…”
Section: Introductionmentioning
confidence: 99%